A survey on electricity market design: Insights from theory and real-world implementations of capacity remuneration mechanisms - Andreas Bublitz; Dogan Keles; Florian Zimmermann; Christoph Fraunholz; Wolf Fichtner (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2018)
Electricity markets are currently going through a phase of agitating transition, which is mainly characterized by an increasing share of fluctuating renewable energies. Among policy makers, this has led to growing concerns about generation adequacy and often to the introduction of different capacity remuneration mechanisms to generate less volatile sources of income for investors and, thereby, guaranteeing generation adequacy. However, these mechanisms entail new challenges regarding the best design to avoid any adverse effects. At the same time, it is disputed whether capacity remuneration mechanisms are indeed needed or whether an energy-only market is sufficient. Therefore, after discussing the peculiarities of the electricity markets, which are the starting point of the unique regulatory framework, an up-to-date overview of the debate on the need for capacity remuneration mechanisms is provided. In addition, the current status of capacity remuneration mechanisms in Europe is shown, and initial experience is presented. Furthermore, this article reflects the current state of research about capacity remuneration mechanisms in regards to, for example, cross-border effects, investment cycles or market power. In a conclusive summary, shortcomings of the existing research works and open questions that need to be addressed in future works are discussed.
urn:nbn:de:swb:90-800634
Keywords: 330; Electricity market; Market design; Generation adequacy